Influence of seed rate and method of sowing on the performance of Bilatidhonia (Eryngium foetidum L.) - Mozumder, SN; Moniruzzaman, M; Rahman, SMM; Sarker, PC; Faisal, SM (Bangladesh Journal of Agricultural Research, 2010)
A field experiment was conducted at ARS, Raikhali, Rangamati during October, 2003 to July 2005 to determine the optimum spacing and seed rate to maximize yield and profitability of Bilatidhonia (Eryngium foetidum L.). A factorial randomized complete block design was followed consisting four methods of sowing (D1 = broadcast, D2 = line sowing (10 cm), D3 = line sowing (15 cm), and D4 = line sowing (20 cm) and three levels of seed rate viz., S1 = 20, S2 = 30, and S3 = 40 kg/ha. Broadcasting and closer spacing (10 cm) with 40 kg seeds/ha showed better performance in respect of yield, yield attributes and profitability. The maximum number of plants/rn2 (590), fresh yield (46.89 t/ha), gross return (Tk. 1031 thousand), gross margin (Tk. 858.1 thousand/ha) and benefit cost ratio (5.32) were obtained from broadcast method of sowing with 40 kg-seed/ha. Keywords: Seed rate and method of sowing; Eryngium foetidum. DOI: 10.3329/bjar.v35i2.5885 Bangladesh J. Agril. Res. 35(2) : 227-234, June 2010